Evaluation of lentiviral based gene delivery system in adherent and suspension in vitro cell models - Mohd Idris, Izyan; Nordin, Fazlina; Muhamad, Nur Jannaim; Idris, Siti Zuleha; Tye, Gee Jun; Wan Kamarul Zaman, Wan Safwani; Ng, Min Hwei (Penerbit Universiti Kebangsaan Malaysia, 2024)
Lentiviruses are a highly robust gene delivery system capable of in vitro and in vivo gene transfer into multiple cell types. Recent fourth-generation lentiviral systems have been designed for enhanced safety, however, the increased recombination events required to produce infective lentiviral particles may reduce production efficiency. A set protocol for all types of target cells is not recommended and optimization of conditions for gene transfer into different target cells is required. In this study, we aim to evaluate the efficiency and reproducibility of lentiviral production using a fourth-generation lentiviral packaging system and identify optimal parameters for successful transduction in two different cell models, adherent and suspension cells. Lentiviral production, effect of viral volume, sustained gene expression and transduction adjuvants on adherent and suspension gene- cell models were evaluated. Transfection and transduction efficiency of lentiviruses was evaluated by fluorescence microscopy and flow cytometry. This study demonstrates that production of green fluorescent protein (GFP)- lentiviruses using the fourth-generation lentiviral packaging is consistent and reproducible. Optimal transduction of adherent cell types is achieved at lower multiplicity of infection (MOI) compared to suspension cells and produces GFP-expressing cells with higher intensity. Expression of GFP is sustained in all cell types over multiple passages. Polycation DEAE-dextran was determined to improve transduction in suspension cells, however, provides similar transduction efficiency as polybrene in adherent cells. In conclusion, fourth generation lentiviral system reproducibly generates high titre lentiviruses capable of infecting multiple cell types, however transduction protocols for different cell types require further optimization.